INTERVENTION PROGRAMS IN THE MONETARY POLICY OF THE EUROSYSTEM (Polityki Europejskie, Finanse i Marketing)
This article presents the underlying legal and economic bases of so-called quantitative easing (QE) in the monetary policy of the Eurosystem. Large asset purchase programs and other intervention purchases of securities are discussed, and the risks of such policies for the long-term stability of the financial system are also addressed. It is noted that the non-standard financial instruments which are used in the Eurozone require close monitoring by Polish government financial institutions. This would help Poland access the full range of financial instruments that could be used to neutralize any unfavorable developments in the national financial sector and in the Polish economy which might occur in a global economic crisis. The research is based on analysis of European Central Bank documents and analytical studies of the Polish National Bank concerning non-standard instruments of financial policy.